Research of Deflection System Magnetic Field Approximation - Čepulis, V.; Navikas, D.; Čepulis, M. (Elektronika ir Elektrotechnika, 2007)
Approximation of magnetic field of deflection system using powmodeling accuracy is analyzed here.